2004
DOI: 10.1093/tropej/50.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Brucellosis--a Microbiological, Epidemiological and Clinical Study

Abstract: A total of 5726 blood specimens (from children aged 14 years and younger) were studied for the serological evidence of brucellosis. Ninety-three (1.6 per cent) showed diagnostic agglutinin titres with a geometric mean titre of 403 (SD +/- 547). Forty-three (59.7 per cent) blood specimens yielded the growth of Brucella melitensis. Thirty-nine patients (41.93 per cent) were shepherds, who constituted the major occupational group affected in the present series. More than 60 per cent of the patients had a history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
62
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 0 publications
13
62
1
6
Order By: Relevance
“…They have also showed no incidence of Brucella antibodies in healthy individuals. 10 similar findings has been recorded in the present study. In a study by Roy et al, (1965) out of 351 samples screened, 21 were positive in diagnostic titres (6%).…”
Section: The Control Groupsupporting
confidence: 93%
See 1 more Smart Citation
“…They have also showed no incidence of Brucella antibodies in healthy individuals. 10 similar findings has been recorded in the present study. In a study by Roy et al, (1965) out of 351 samples screened, 21 were positive in diagnostic titres (6%).…”
Section: The Control Groupsupporting
confidence: 93%
“…In a study by Roy et al, (1965) out of 351 samples screened, 21 were positive in diagnostic titres (6%). 10 Joshi and Omprakash screened 800 samples and have found diagnostic titres in 39 cases (4.9%) 11 . In study by Gokhale et al, (1999) out of 72 patients 6 were Seropositive for brucellosis (8.3%).…”
Section: The Control Groupmentioning
confidence: 99%
“…Nevertheless, the highest cure rate can be achieved with a triple therapy (3) and adding a third drug to the standard regimen seems to be beneficial (63). In two reports, children treated with three drugs had a better outcome than those treated with two drugs (65,66). Almost 84% of the patients in the present study were treated with a combination of three antimicrobial agents, based on our previous experience that three-drug therapy was better than two-drug therapy (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…This is because the occupations described in this study are male dominated in Bangladesh. Several other studies have indicated gender as significant risk factors for brucellosis (Wassif et al, 1992;Shehata et al, 2001;Mantur et al, 2004;Meky et al, 2007).…”
Section: Rahman Et Almentioning
confidence: 94%